Encyclopedia of RF and Microwave Engineering 2005
DOI: 10.1002/0471654507.eme573
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance Extraction

Abstract: With the advances in integrated circuit (IC) technology, the effects of electromagnetic coupling among the metal interconnect lines have greatly influenced circuit performance in both VLSI circuits and microwave ICs. Therefore, the modeling and accurate extraction of interconnect capacitance has become a subject of advanced research in these fields. In this article, the fundamental theory, contemporary methodology, and algorithms of capacitance extraction are presented. First, the electrostatic basis of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…A remarkable interest in the techniques for efficient numerical simulation of three‐dimensional large‐scale electrostatic problems exists. In recent years, for example, the accurate extraction of parasitic circuit parameters for the analysis of the performance and the signal integrity of semiconductor devices and interconnections in integrated circuits (IC) has become fundamental, see for example 1–4. The strong industrial interest is demonstrated by the number of papers and commercial tools dedicated to this purpose 5–12.…”
Section: Introductionmentioning
confidence: 99%
“…A remarkable interest in the techniques for efficient numerical simulation of three‐dimensional large‐scale electrostatic problems exists. In recent years, for example, the accurate extraction of parasitic circuit parameters for the analysis of the performance and the signal integrity of semiconductor devices and interconnections in integrated circuits (IC) has become fundamental, see for example 1–4. The strong industrial interest is demonstrated by the number of papers and commercial tools dedicated to this purpose 5–12.…”
Section: Introductionmentioning
confidence: 99%
“…The 2.5-D extraction method refers to the method considers 3-D geometric effects on capacitance with 2-D interconnect patterns through sweeping 3-D geometry of interconnects in two perpendicular directions [16], [17]. It is adopted by the OpenROAD project for parasitic extraction [18]…”
Section: A Full-chip Capacitance Extraction Based On Pattern Matching...mentioning
confidence: 99%
“…Rozwiązanie analityczne rozpatrywanego zagadnienia jest moŜliwe jedynie dla szczególnych, prostych konfiguracji, dlatego teŜ w większości przypadków stosuje się metody numeryczne ( [15,23]), w tym coraz częściej metody brzegowe (MB). Stosowane techniki brzegowe to głównie odmiany metody elementów brzegowych (MEB) w postaci tak pośredniej jak i bezpośredniej [7].…”
Section: Wprowadzenieunclassified